Scholarly activity in Canadian Residency Matching Service criteria: do Canadian programs really care about applicant research? - Asil El Galad; Hanna Van Dierdonck; Nikesh Chander; Caleb Mathai; Alyssa Palmateer; Shenna Dunn; Seddiq Weera; Larry W Chambers; Amanda Bell (Canadian Medical Education Journal)
Background: Residency programs across Canada evaluate applicants based on written applications, reference letters, and interviews. One key factor many institutions consider is “scholarly activity.” To improve transparency, the Canadian Residency Matching Service (CaRMS) recently revised its program description pages, adding a dedicated section outlining expectations for research and academic work. This study examines whether these changes have made program criteria clearer for applicants.